Performance and emissions analysis of jatropha and aphanamixis polystachya methyl esters and investigation of NOx additive in CI diesel engine / Md Palash Sarker - Md Palash , Sarker (2017)
Biodiesel fuels have the potential to become a reliable substitute for diesel which is used moderately to meet the current energy demands. This fuel can be produced from new or used vegetable oils, non-edible sources and animal fats, which are non-toxic, biodegradable and renewable. In spite of the many advantages of using biodiesel, most of the researchers have reported that biodiesel produce higher NOx emissions compared to diesel, which is a deterrent to the market expansion of these fuels. This study presents the prospect of biodiesel derived from non-edible oil Aphanamixis polystachya oil and Jatropha oil in diesel engine. The study deals with the physicochemical properties of Aphanamixis polystachya methyl ester (APME), Jatropha methyl ester (JME) and their individually blends with diesel followed by evaluation of performance and emission characteristics in a multi-cylinder diesel engine. From the literature review, it was found that the average reduction of NOx emissions by using additives, exhaust gas recirculation (EGR), water injection (WI) & emulsion technology (ET), injection timing retardation ( ITR), simultaneous technology (ST) and low temperature combustion (LTC) are in the ranges 4-45%, 26-84%, 10-38%, 9.77-37%, 22-95% and 66-93% respectively, compared to biodiesel combustion without applying NOx reduction technologies. Among all NOx reduction technologies, Fenimore mechanism explains that fuel radicals formed during the combustion process react with nitrogen from the air to form NOx. It can be proposed that if these radical reactions could be terminated, NOx formation rate for biodiesel combustion would decrease. An experimental study was conducted on a four cylinder diesel engine to evaluate the performance and emission characteristics of Jatropha biodiesel blends (JB5, JB10, JB15 and JB20) with and without addition of N, N′-diphenyl-1, 4-phenylenediamine (DPPD) antioxidant. From test results, it has been observed that the properties of biodiesel and its blends are compatible with the ASTM D 6751 and ASTM D7467 standards, respectively. It was found that, APME5 and APME10 showed an average 0.9% and 1.81% reduction in torque and 0.9% and 2.1% reduction in brake power (BP), and 0.87% and 1.78% increase in brake specific fuel consumption (BSFC) compared to diesel. In the case of engine emissions, diesel blends of APME gave an average reduction in carbon monoxide (CO) and hydrocarbon (HC) emissions but emitted higher levels of nitrous oxide compared to diesel. It was found that, JB5, JB10, JB15 and JB20 showed an average 3.92%, 4.41%, 3.86% and 4.91% reduction in torque and 0.8%, 1.68%, 2.84% and 3.68% reduction in brake power (BP), and 6.80%, 8.33%, 10.70% and 11.30% increase in brake specific fuel consumption (BSFC) compared to diesel. In the case of engine emissions, diesel blends of Jatropha biodiesel gave an average reduction in carbon monoxide (CO) and hydrocarbon (HC) emissions but emitted higher levels of nitrous oxide compared to diesel. For Jatropha biodiesel blends, the results showed that DPPD antioxidant additive could reduce NOx emission significantly with slight penalty of engine performance as well as CO and HC emissions. By addition of 0.15% (m) DPPD additive in JB5, JB10, JB15 and JB20, reduction of NOx emission were 8.03, 3.503, 13.65 and 16.54% respectively, compared to biodiesel blends without additive at full throttle position. These results suggested that the addition of antioxidant additives in biodiesel blends reduces NOx emission which can solve the barrier to its market expansion.